2008
DOI: 10.1016/j.jacc.2007.11.085
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Utility of B-Type Natriuretic Peptide Assessment in Stable Low-Risk Outpatients With Nonischemic Cardiomyopathy After Decompensated Heart Failure

Abstract: Even in stable low-risk outpatients with NICM at 6 months after hospital discharge for decompensated HF, BNP assessment predicts a long-term risk of redecompensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 35 publications
3
40
0
2
Order By: Relevance
“…There is no generally accepted level of BNP by stable heart failure patients with optimal medical therapy which would clearly present a dividing line for prognosis setting. Criterium of BNP being higher than median, which was 210 pg/mL, corresponds relatively well with the values characterising poor prognosis in relatively comparable data files 23,24 . These data confirm the significance of present BNP and pVO2 use in prognostic stratification 24 .…”
Section: Discussionsupporting
confidence: 78%
“…There is no generally accepted level of BNP by stable heart failure patients with optimal medical therapy which would clearly present a dividing line for prognosis setting. Criterium of BNP being higher than median, which was 210 pg/mL, corresponds relatively well with the values characterising poor prognosis in relatively comparable data files 23,24 . These data confirm the significance of present BNP and pVO2 use in prognostic stratification 24 .…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have shown a correlation between higher BNP levels and worsening HF classes and measures of functional status. 6,13,19 These studies included subjects with HF classes I to IV, whereas in the current study, 72% of the subjects had HF class II and 27% had HF class III or IV, with Survival analysis of time to hospitalization for worsening HF, death, or transplant showed significantly worse event-free survival in subjects with BNP Ն140 pg/mL. Event-free survival at 6 and 9 months was 90% and 78%, respectively, for a BNP level Ͻ140 pg/mL and 68% and 50%, respectively, for a BNP level of Ն140 pg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Although these data are consistent with previous studies showing that BNP levels can predict adverse outcomes in both children and adults with HF, further validation is needed to determine the BNP level necessary to stratify risk in other specific and/or broader cohorts. 15,19 In a cohort of mostly asymptomatic older children, all of whom had a diagnosis of dilated cardiomyopathy with anatomically normal hearts, Price et al 15 reported a positive association of a BNP level of 300 pg/mL with a 90-day composite outcome of HF-related hospitalization, HF-related death, or listing for transplantation. Our study population was very different in that all subjects were symptomatic and 40% of the subjects had a diagnosis of CHD, 27% with a non-LV systemic ventricle.…”
Section: Auerbach Et Al Bnp Predicts Pediatric Heart Failure Outcomesmentioning
confidence: 99%
“…After the treatment, the predischarge cutoff point for the risk of readmission and mortality falls to about 500 pg/ml (12). The cutoff point further declined to abut 200 pg/ml in clinically stable outpatients after decompensated HF (13). These obsevations suggested that the therapeutic strategies for HF including a safe hospital discharge and the prevention of readmission or cardiac event may be guided by BNP measurement.…”
Section: Heart Failurementioning
confidence: 99%
“…Recently, we reported prognostic utility of BNP in clinically stable 83 outpatients with nonischemic DCM after decompensated HF (13). They were in a clinically stable status during at least 6 months after hospital discharge at relatively low BNP level, namely mean BNP level of about 200 pg/ml.…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%